International Migration Intentions and Illegal Costs: Evidence from Africa-to-Europe Smuggling Routes - Guido Friebel; Miriam Manchin; Mariapia Mendola; Giovanni Prarolo (Institute of Labor Economics (IZA), 2018)
Irregular migrants from Africa and the Middle East flow into Europe along land and sea routes under the control of human smugglers. The demise of the Gaddafi regime in 2011 marked the opening of the Central Mediterranean Route for irregular border - crossing between Libya and Italy. This resulted in the immediate expansion of the global smuggling network, which produced an asymmetric reduction in bilateral distance between country pairs across the Mediterranean sea. We exploit this source of spatial and time variation in irregular migration routes to estimate the elasticity of migration intentions to illegal moving costs proxied by distance. We build a novel dataset of geolocalized time-varying migration routes, combined with cross-country survey data on individual intentions to move from Africa (and the Middle East) into Europe. Netting out any country-by-time and pair-level confounders we find a large negative effect of distance along smuggling routes on individual migration intentions. Shorter distances increase the willingness to migrate especially for youth, (medium) skilled individuals and those with a network abroad. The effect is stronger in countries closer to Libya and with weak rule of law.
Keywords: K23; K42; 330; international migration; human smuggling; illegal migration; Libyan Civil War